Communitarian Legal Pluralism (CLP) and the International Criminal Court (ICC): Toward a Hybrid Justice Model for Mass Atrocity Crimes - Berebon, Charles (dialektika kontemporer, 2025)
The International Criminal Court (ICC) has long faced criticism for its perceived disconnect from the communities most affected by mass atrocities, with critiques centering on its Western-centric legal framework, punitive focus, and limited engagement with localized justice traditions. This paper proposes a transformative approach by applying Communitarian Legal Pluralism (CLP) to reconceptualize the ICC’s role in transitional justice. CLP, which recognizes the coexistence and legitimacy of multiple legal orders, offers a framework for integrating customary, Indigenous, and restorative justice mechanisms into international criminal proceedings. Through comparative analysis of case studies—including Rwanda’s gacaca courts, Uganda’s mato oput, and Colombia’s hybrid peace tribunals—we argue that a CLP-informed ICC could bridge the gap between global accountability and localized reconciliation. The study examines three key dimensions: (1) how subsidiarity principles could allow the ICC to defer to community-based justice where appropriate, while intervening only when local mechanisms fail to address grave human rights violations; (2) the potential for pluralist sentencing that incorporates reparative measures rooted in victims’ cultural norms; and (3) institutional reforms to enhance victim participation through culturally meaningful procedures. We demonstrate that such a hybrid model would not only strengthen the ICC’s legitimacy but also advance more sustainable post-conflict healing, as seen in cases where restorative practices outperformed retributive justice in fostering social cohesion. Challenges—including tensions between universal human rights standards and cultural relativism, as well as risks of elite capture in customary systems—are critically analyzed. The paper concludes with policy recommendations for a